The Value of Anesthesiology in Undergraduate Medical Education as Assessed by Medical School Faculty - Euliano, Tammy Y; Robicsek, Steven A; Banner, Michael J (The journal of education in perioperative medicine, 2010)
Unlike Europe and Canada, the majority of American medical schools do not require an anesthesiology rotation. Yet the skill set and knowledge base of anesthesiologists includes many topics of importance to all physicians. Furthermore, the clinical environment offers more procedural experience and real-time physiology and pharmacology for teaching than that available elsewhere. Medical schools, however, often focus on "general medical education" and discount the value of a required anesthesiology clerkship. This begs the question, of the topics anesthesiologists excel at teaching, which are considered important by faculty across the spectrum of medical specialties? Two-hundred-three senior medical students rated the importance to their career of 14 topics currently taught by lecture, simulation or reading assignment in the required anesthesiology curriculum at the University of Florida. Specialty faculty in each of the major specialties similarly rated the topics. The authors compared these with the opinion of 20 anesthesiology faculty who rated the importance of each topic for each major specialty. Overall, acute pain management and acute decompensation management were rated "somewhat" or "very important" by the highest proportion of respondents; followed closely by vascular access and fluid management, non-invasive monitoring and conscious sedation. The topics of interest to surgeons most closely aligned with those offered (12/14 rated somewhat or very important by >75% of faculty polled, 14/14: students), followed by emergency medicine physicians (10/14: faculty, 11/14: students). Significant differences of opinion existed between all three groups on several topics. Anesthesiologists excel in topics important to all future physicians; as many schools enter a new phase of curricular redesign, a rotation in anesthesiology should receive serious consideration. The input of students and physicians in major medical specialties may help define an appropriate curriculum. Including the flexibility for students to adapt that curriculum to individual goals may increase the rotation's value.